1990
DOI: 10.1128/aac.34.6.1132
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of the triazole Bay R 3783 in mouse models of coccidioidomycosis, blastomycosis, and histoplasmosis

Abstract: A new triazole, Bay R 3783, was compared with ketoconazole, itraconazole, and fluconazole, which were given via the alimentary tract at three dosages, and amphotericin B, which was given at 1 mg/kg intraperitoneally, in murine models of the systemic mycoses coccidioidomycosis, histoplasmosis, and blastomycosis. In a pulmonary coccidioidomycosis model, Bay R 3783, fluconazole, and itraconazole were essentially equally efficacious and more active than ketoconazole in protecting mice against death; but they were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…This model differs from those reported previously (7,15,27) in the method of central nervous system (CNS) infection and the form of the organism used for infection. The model mimics the disease in humans and appears to be appropriate for the testing of therapy.…”
contrasting
confidence: 45%
See 1 more Smart Citation
“…This model differs from those reported previously (7,15,27) in the method of central nervous system (CNS) infection and the form of the organism used for infection. The model mimics the disease in humans and appears to be appropriate for the testing of therapy.…”
contrasting
confidence: 45%
“…For the analysis of the fungal burdens in the surviving animals, a value of 8 log 10 CFU/g was given to missing datum points (due to the death of the animal) (21,27). Horizontal lines, median log 10 of numbers of CFU/g tissue; * , P Ͻ 0.001 versus the results for the control; †, P Ͻ 0.05 for the results for ICZ versus the results for FCZ at 25 mg/kg; ‡, P Ͻ 0.005 for the results for ICZ versus the results for FCZ at 25 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Kobayashi et al reported that, in a mouse model, FLC was more effective against histoplasmosis caused by a highly FLC-resistant strain (MIC for the Y form, Ͼ1,000 g/ml) than against that caused by a susceptible strain (MIC for the Y form, 0.78 g/ml) (13). Pappagianis et al demonstrated that three azole drugs had comparable efficacies against a murine pulmonary infection by C. immitis for which the MICs (for either spherules or endospores) of the three drugs were considerably different (0.25, 1.0, and Ͼ64 g/ml) and concluded that the results of the in vitro susceptibility tests for this fungus were not predictive of therapeutic outcome (23). In addition, notwithstanding that the Y forms of H. capsulatum and B. dermatitidis showed relatively high susceptibility to FLC in this study (Candida isolates for which the MIC of FLC is 8 g/ml or lower are categorized as susceptible), FLC is described as having poor clinical efficacy against histoplasmosis and blastomycosis (15).…”
Section: Discussionmentioning
confidence: 99%
“…Mice were infected intracerebrally according to a previously published model (20,21) for the CNS studies. Briefly, anesthetized mice were inoculated through the calvarium with a target dose of 90 spores in 30 l of saline.…”
Section: Methodsmentioning
confidence: 99%